People are increasingly bored in our digital age - Katy Y. Y. Tam; Michael Inzlicht (Communications Psychology)
Abstract In an era where entertainment is effortlessly at our fingertips, one would assume that people are less bored than ever. Yet, reports of boredom are higher now than compared to the past. This rising trend is concerning because chronic boredom can undermine well-being, learning, and behaviour. Understanding why this is happening is crucial to prevent further negative impacts. In this Perspective, we explore one possible reason—digital media use makes people more bored. We propose that digital media increases boredom through dividing attention, elevating desired level of engagement, reducing sense of meaning, heightening opportunity costs, and serving as an ineffective boredom coping strategy.